Mutual Transformations of State and Traditional Authority. The renewed role of chiefs in policing and justice enforcement in Mozambique - Kyed, Helene (2011)
This article explores the renewed role of chiefs in policing and justice enforcement from the perspective of every-day practices and modes of organising the relationship between chiefs and local state institutions. Based on ethnographic material from Dombe in Sussundenga District, in Mozambique, it asks what the newly forged relationship implies for local state and traditional authority. The article shows that the Decree 15/2000 was appropriated by the local tiers of state police not as a benign recognition of already existing chiefly practices, but as a means to regulate chiefs and bolster state authority in the former war-zone of Dombe.